PENGARUH KESESUAIAN TUGAS-TEKNOLOGI, KEPERCAYAAN DAN EFEKTIVITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA INDIVIDU PADA PASARSWALAYAN DI KOTA TANGERANG - Agnes Ashianti (Jurnal Bina Akuntansi, 2017)
The objective of this research is to examine the effect of task-technology fit, trust of accounting information systems, and effectiveness of accounting information systems on the individual performance at a supermarket in Tangerang city. The samples in this study were employees of a supermarket in Tangerang city who used accounting information system in doing its job. The data used in this study is primary data through questionnaires. In data analysis techniques, this study test the reliability of the formula coefficient of Cronbach 's Alpha, validity test by means of correlation using the r counted and r table, test for normality using Kolmogorov-Smirnov test, the classical assumption, hypothesis testing multiple linear regression, t test, and F test. The results showed that the task-technology fit and trust of accounting information systems each have a significant effect on the individual performance, while the effectiveness of accounting information systems does not significantly influence the individual performance. Task-technology fit, trust of accounting information systems, and the effectiveness of accounting information systems have simultaneous significant effect on the individual performance.